Blood pressure control and left ventricular hypertrophy in long-term CAPD and hemodialysis patients: A cross-sectional study - Günal, Ali Ihsan; Ilkay, Erdogan; Kirciman, Ercan; Karaca, Ilgin; Dogukan, Ayhan; Celiker, Huseyin (Multimed Inc., 2003)
? Background: It is still not clear whether hypertension and left ventricular hypertrophy (LVH) are more common in continuous ambulatory peritoneal dialysis (CAPD) than in hemodialysis (HD) patients. ? Methods: To examine this subject, the indices of cardiac performance were compared between 50 HD and 34 CAPD patients. Patients were further divided into two subgroups [long-term (L) CAPD and L-HD] according to dialysis modality and duration of dialysis (more than 60 months' duration). ? Results: The blood pressure and cardiothoracic index of CAPD patients did not differ from HD patients. On average, the left atrial index was 2 mm/m2 higher in HD patients than in CAPD patients. Left ventricular chamber sizes, wall thickness, and left ventricular mass index (LVMI) in patients on CAPD were similar to those of HD patients. Isovolumic relaxation time (IVRT) of CAPD patients was insignificantly less than that of HD patients (101 ± 22 and 115 ± 27 msec respectively). There was no significant difference between the two subgroups (L-HD and L-CAPD) in blood pressure, left atrial diameter, left ventricular chamber size, wall thickness, LVMI, ejection fraction, or IVRT. ? Conclusion: If normovolemia and normotension are obtained by strict volume control without using antihypertensive drugs, the effects of the two modalities of chronic dialysis treatment (HD and CAPD) on cardiac structure and function are not different from each other.
Keywords: Echocardiography; Hemodialysis; Left ventricular hypertrophy; Strict volume control